2016
DOI: 10.1186/s12879-016-1950-z
|View full text |Cite
|
Sign up to set email alerts
|

Environmental contamination and risk factors for transmission of highly pathogenic avian influenza A(H5N1) to humans, Cambodia, 2006-2010

Abstract: BackgroundHighly pathogenic avian influenza A (H5N1) virus has been of public health concern since 2003. Probable risk factors for A(H5N1) transmission to human have been demonstrated in several studies or epidemiological reports. However, transmission patterns may differ according to demographic characteristics of the population and local practices. This article aggregates these data from three studies with data collected in the previous surveys in 2006 and 2007 to further examine the risks factors associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Previous research has shown that agricultural producers including poultry farmers identify animal waste management as important to preventing disease ( 45 , 46 ), particularly where there is contact with water associated with agricultural production ( 16 , 19 , 20 ). Interestingly, we also found consistency in previous research with the perception of many of our respondents that HPAI cannot happen to them ( 27 , 45 ). Although there was some evidence in previous research that some strata of small scale farmers do not mitigate against EIDs, this seems to be associated with a result of lack of risk awareness ( 16 , 18 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous research has shown that agricultural producers including poultry farmers identify animal waste management as important to preventing disease ( 45 , 46 ), particularly where there is contact with water associated with agricultural production ( 16 , 19 , 20 ). Interestingly, we also found consistency in previous research with the perception of many of our respondents that HPAI cannot happen to them ( 27 , 45 ). Although there was some evidence in previous research that some strata of small scale farmers do not mitigate against EIDs, this seems to be associated with a result of lack of risk awareness ( 16 , 18 ).…”
Section: Discussionsupporting
confidence: 89%
“…The intention has been to limit the role of water to act as a reservoir for influenza viruses, as well as reduce risk of transmission of between species (including humans), rather than prevent direct infection via pond or well water which is rare for H5N1. Nevertheless, direct infection via water has been reported ( 27 , 28 ) and risk increases with bathing in communal ponds or working in contaminated fish ponds, for example, both of which are common activities in rural Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…Influenza A virus (IAV) is highly infectious, and causes significant morbidity and mortality worldwide ( Ly et al, 2016 ; Marinova-Petkova et al, 2016 ; Thomas et al, 2017 ). Highly pathogenic avian influenza virus (H5N1-HPAIV) has been categorized as a List A disease by the International Office of Epizootics (OIE).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that contamination of poultry-related environments, including live poultry markets (LPMs) and backyard poultry flocks, is a major risk factor for human AIV [ 12 , 13 ]. Previous studies have reported differences in the poultry exposure to AIV between urban and rural areas.…”
Section: Introductionmentioning
confidence: 99%